2022
DOI: 10.1108/techs-04-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

The green design of high-rise buildings: how is the construction industry evolving

Abstract: PurposeGreen building, which is also commonly referred to as sustainable building, is focused on the processes implemented that are environmentally efficient and responsible throughout the life cycle of the building. This accounts for the time of manufacturing of materials, to the erection of these materials, on-site, to the operation of the building and how these efficient materials assist in the operation and running of the building daily, all the way through to the demolition. There are many aspects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Ref. [20] identified that hemp is an extremely durable plant that requires unique processing to transform it into a usable building material. After its unique processing period, it is generally mixed with lime to create strong, yet lightweight insulating concrete.…”
Section: Present Green Building Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [20] identified that hemp is an extremely durable plant that requires unique processing to transform it into a usable building material. After its unique processing period, it is generally mixed with lime to create strong, yet lightweight insulating concrete.…”
Section: Present Green Building Processesmentioning
confidence: 99%
“…Refs. [20,21] further investigated this material in broad depth and found that hemp concrete is classified as a non-load-bearing material that it is generally used in conjunction with wood, steel, and concrete frameworks. Additionally, after testing, the authors in [22] were able to show that hemp concrete does indeed fit the characteristics of green building material; however, the quality of its environmental friendliness can be improved by reducing the impact caused by the binder.…”
Section: Present Green Building Processesmentioning
confidence: 99%